2010
DOI: 10.5114/pg.2010.17265
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing prevalence of Helicobacter pylori infection in children in Poland

Abstract: StreszczenieWstęp: Ostatnie duże badania dotyczące częstości zakażeń Helicobacter pylori (H. pylori) u dzieci w Polsce były prowadzone prawie 10 lat temu. Poprawa średnich przychodów i warunków życia w ciągu ostatnich lat pozwala przypuszczać, że odsetek za każeń H. pylori u dzieci powinien wykazywać stały trend spadkowy. Cel: Ocena aktualnej częstości występowania zakażenia H. pylori w populacji ogólnej dzieci szkolnych niemających objawów, zamieszkałych na terenach miejskich Górnego Śląska. Ocena wpływu wybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 15 publications
5
13
1
Order By: Relevance
“…Whether Hp prevalence in young type 1 diabetes patients is higher than in the general population remains controversial [19][20][21]. Although not addressed in the present study, recent studies in Poland report a lower (∼16%) infection rate in healthy children [22]. Thus, Hp infection may be associated with type 1 diabetes independently of parietal cell autoimmunity.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Whether Hp prevalence in young type 1 diabetes patients is higher than in the general population remains controversial [19][20][21]. Although not addressed in the present study, recent studies in Poland report a lower (∼16%) infection rate in healthy children [22]. Thus, Hp infection may be associated with type 1 diabetes independently of parietal cell autoimmunity.…”
Section: Discussionmentioning
confidence: 72%
“…With respect to Hp, we found no association of the UBC measures with any of the parameters examined. Although epidemiological studies suggest that the prevalence of Hp infection increases with age [22], research conducted in type 1 diabetes subjects does not support this finding [18,20,25]. The negative association of Hp with HbA1c has also been documented by other investigators [19,20,25].…”
Section: Discussionmentioning
confidence: 97%
“…It was found that the average rate of H. pylori infections in Polish children was 34.5% [4]. Data from the year 2008 from the region of Silesia showed a drop in the rate of H. pylori infection in healthy children (15.7%) [20,21]. In that study, the average prevalence of H. pylori infection in children with clinical symptoms was similar to observations made in children with abdominal pain in the Pomerania region (16.5%) [22], and were consistent with the observations of other authors in Central and Eastern Europe [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of the Helicobacter pylori infection differs worldwide among the paediatric population. It has decreased in some countries, especially high‐income countries, and some authors have attributed this to improvements in socio‐economic status .…”
Section: Discussionmentioning
confidence: 99%
“…Another reason for more considerable Helicobacter pylori testing and treatment in children is the declining incidence observed in some countries . Since 1992, when the results of the first Polish epidemiological study were published, the prevalence of Helicobacter pylori among children has more than halved, from above 40% to approximately 15% in 2006 and 2010 .…”
Section: Introductionmentioning
confidence: 99%